Until we find home [large type] - Gohlke, Cathy (Thorndike Press, a part of Gale, a Cengage Company, 2018)
"As Hitler marches across Europe, citizens in the bucolic Lake District of England fight a quieter war of their own, taking in child refugees while preparing for the ever-looming threat of Nazi invasion of their peaceful haven"--|cProvided by publisher.